Association of Single-Nucleotide Polymorphisms of rs2383206, rs2383207, and rs10757278 With Stroke Risk in the Chinese Population: A Meta-analysis - Hu, Xuemei; Wang, Dongsen; Cui, Chunying; Wu, Qingjian (Frontiers in Genetics, 2022)
Several studies have demonstrated that Chromosome 9p21 was associated with ischemic stroke (IS) risk significantly, with the allele G increasing the risk. However, published literature reports controversial results. We systematically assessed that stroke have a relationship with three loci (rs2303206, rs2383207 and rs10757278) on chromosome 9P21 in a meta-analysis. We searched PubMed and Embase databases for relevant studies. Calculate OR value was performed with the chi-square test. Evaluation of experimental data can be performed using bias tests and sensitivity analysis. We analyzed data from 16 studies involving 27,792 individuals of Chinese ancestry, including 13,522 cases and 14,275 controls. The results that odds ratio (OR) was 1.15, 95% confidence interval (CI): (1.11, 1.20) P＜0.0001. The correlation between 9P21 chromosome and IS in Chinese population was verified by us. Because three single nucleotide polymorphisms (SNPS) have a chain disequilibrium relationship, so loci rs2383206, rs2383207 and rs10757278 may increase the risk of IS.